MicroRNAs contribute to enhanced salt adaptation of the autopolyploid Hordeum bulbosum compared with its diploid ancestor. (12th May 2017) - Liu, Beibei; Sun, Genlou
Summary: Several studies have shown that autopolyploid can tolerate abiotic stresses better than its diploid ancestor. However, the underlying molecular mechanism is poorly known. microRNAs (miRNAs) are small RNAs that regulate the target gene expression post‐transcriptionally and play a critical role in the response to abiotic stresses. Duplication of the whole genome can result in the expansion of miRNA families, and the innovative miRNA–target interaction is important for adaptive responses to various environments. We identified new microRNAs induced by genome duplication, that are also associated with stress response and the distinctive microRNA networks in tetraploid and diploid Hordeum bulbosum using high‐throughput sequencing. Physiological results showed that autotetraploid Hordeum bulbosum tolerated salt stress better than its diploid. Comparison of miRNAs expression between diploid and tetraploid check (CK) and salt stress revealed that five miRNAs affected by genome doubling were also involved in salt stress response. Of these, miR528b‐3p was only detected in the tetraploid, and downregulated under salt stress relative to that in tetraploid CK. Moreover, through target prediction, it was found that miR528b‐3p was not only involved in DNA replication and repair but also participated in salt stress response. Finally, by analyzing all the differentially expressed microRNAs and their targets, we also discovered distinguished microRNAs–target regulatory networks in diploid and tetraploid, respectively. Overall, the results demonstrated the critical role of microRNAs in autopolyploid to have better tolerance salt stress. Significance Statement: Our results shed light on the mechanism underlying how autopolyploid can better adapt to adverse environments compared with its diploid ancestor from the microRNAs perspective. Moreover, the distinctive microRNA—targets regulatory networks in tetraploid and diploid can help us better understand the evolutionary significance of the autopolyploid.